DONASI DAN BHAKTI SOSIAL BAGI MASYARAKAT CILEUNYI WETAN TERDAMPAK COVID 19 (UPAYA MEMUTUS MATA RANTAI WABAH COVID 19) - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Noneng Nurhayani, Noneng Nurhayani; Rahmi Rismayani Deri, Rahmi Rismayani Deri; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Syahroni Mustofa, Syahroni Mustofa (Media Nusantara, 2021)
COVID-19, short for Coronavirus Disease 2019, is caused by the novel coronavirus SARS-CoV-2. This virus emerged in Wuhan, China. In early January 2020, Chinese authorities identified a new coronavirus, which was later named SARS-CoV-2 due to its genetic similarity to the SARS (Severe Acute Respiratory Syndrome) virus. Global Spread: In January 2020, cases of COVID-19 were reported in several countries, leading the World Health Organization (WHO) to declare it a Public Health Emergency of International Concern on January 30, 2020. Pandemic Declaration: On March 11, 2020, WHO declared COVID-19 a pandemic because the virus had spread globally, affecting many countries and causing significant illness and death. Global Response: Governments around the world implemented a variety of measures to control the spread of the virus, including lockdowns, travel restrictions, social distancing guidelines, mask mandates, and vaccination campaigns. Impact: COVID-19 has had a major impact on public health, economies and societies around the world. The disease is burdening healthcare systems in many countries, causing disruption to daily life, business, education and travel. Vaccine Development: Efforts to develop a vaccine against COVID-19 began in early 2020. Continuing Variants and Challenges: The virus continues to evolve, causing the emergence of new variants. Long-Term Implications: In mid-2024, COVID-19 will still be a global health problem.